Vitamin C Deficiency May Delay Diet-Induced NASH Regression in the Guinea Pig - Josephine Skat-Rørdam; Kamilla Pedersen; Gry Freja Skovsted; Ida Gregersen; Sara Vangsgaard; David H. Ipsen; Markus Latta; Jens Lykkesfeldt; Pernille Tveden-Nyborg (MDPI AG, 2021)
Oxidative stress is directly linked to non-alcoholic fatty liver disease (NAFLD) and the progression to steaotohepatitis (NASH). Thus, a beneficial role of antioxidants in delaying disease progression and/or accelerating recovery may be expected, as corroborated by recommendations of, e.g., vitamin E supplementation to patients. This study investigated the effect of vitamin C deficiency-often resulting from poor diets low in fruits and vegetables and high in fat-combined with/without a change to a low fat diet on NAFLD/NASH phenotype and hepatic transcriptome in the guinea pig NASH model. Vitamin C deficiency per se did not accelerate disease induction. However, the results showed an effect of the diet change on the resolution of hepatic histopathological hallmarks (steatosis, inflammation, and ballooning) (p < 0.05 or less) and indicated a positive effect of a high vitamin C intake when combined with a low fat diet. Our data show that a diet change is important in NASH regression and suggest that a poor vitamin C status delays the reversion towards a healthy hepatic transcriptome and phenotype. In conclusion, the findings support a beneficial role of adequate vitamin C intake in the regression of NASH and may indicate that vitamin C supplementation in addition to lifestyle modifications could accelerate recovery in NASH patients with poor vitamin C status.